Анализ некоторых экологических особенностей партеногенетических и бисексуальных видов клещей-фитосейид - Колодочка, Л.А. (Вестник зоологии, 1984)
Some basic ecological characteristics of two thelytokous Phytoseiid mites, Amblyseius agrestis and A. herbarius were studied under laboratory conditions: fecundity, feeding activity, pre- and oviposition period duraton, and population growth indices. These species show some differences in studied indices from bisexual A. andersoni, A. reductus and A. longispinosus. The real parameters of population growth in A. agrestis are found to be lower than in other species under consideration.